Vitamin E supplementation, delayed-onset muscular soreness, muscle tissue damage and lipid peroxidation - Harris, M. B. (1995)
Abstract: The purpose of this study was to determine the effects of 48 days of 800 I.U. of vitamin E supplementation on subjective ratings of delayed-onset muscular soreness (DOMS), pressure thresholds (PT), plasma levels of creatine kinase (CK), and plasma levels of thiobarbituric re active substances (TBARS) following a 20 minute bench stepping exercise. Nine experimental subjects completed two trials, one on placebo and the other on vitamin E. Subjective ratings of DOMS, PT, plasma CK and plasma TBARS were measured pre-exercise, imm ediate, 6 24, 48, and 72 hours post-exercise. Results (p20.05) showed a significant reduction in subjective ratings of DOMS following vitamin E supplementation. No significant differences in PT, plasma CK or plasma TBARS were found between the placebo an d vitamin E supplemented trials. It was concluded that although vitamin E upplementation had a significant effect on subjective ratings of DOMS, no clear evidence was found that could explain this difference. (Harris, M.B. Vitamin E supplementation, delayed-onset muscular soreness, muscle tissue damage and lipid peroxidation, 1995. M.A., University of North Carolina at Chapel Hill. (110pp 2f $10.00) PH 1462)